The role of oxytocin in the facial mimicry of affiliative vs. non-affiliative emotions. (November 2019) - Pavarini, Gabriela; Sun, Rui; Mahmoud, Marwa; Cross, Ian; Schnall, Simone; Fischer, Agneta; Deakin, Julia; Ziauddeen, Hisham; Kogan, Aleksandr; Vuillier, Laura
Highlights: Oxytocin plays a role in the modulation of emotional mimicry in ways that are conducive to affiliation. Oxytocin increases mimicry of facial features of sadness (i.e. pouting). Oxytocin facilitates mimicry of happiness for individuals who show low positive expressivity. Automated facial coding can be reliably used to detect emotional mimicry. Abstract: The present paper builds upon a growing body of work documenting oxytocin's role in social functioning, to test whether this hormone facilitates spontaneous mimicry of others' emotional expressions. In a double-blind, randomized trial, adult Caucasian males ( n = 145) received a nasal spray of either oxytocin or placebo before completing a facial mimicry task. Facial expressions were coded using automated face analysis. Oxytocin increased mimicry of facial features of sadness (lips and chin, but not areas around the eyes), an affiliative reaction that facilitates social bonding. Oxytocin also increased mimicry of happiness, but only for individuals who expressed low levels of happiness in response to neutral faces. Overall, participants did not reliably mimic expressions of fear and anger, echoing recent theoretical accounts of emotional mimicry as dependent on the social context. In sum, our findings suggest that oxytocin facilitates emotional mimicry in ways that are conducive to affiliation, pointing to a possible pathway through which oxytocin promotes social bonding.